Assessing chinese hotel employee's motivation and involvement in the context of applying loyalty programme practices in international hotel chains in china - Thorsten Robert Moller (Administrative Sciences, 2024)
To understand how to strengthen employee's loyalty programme (LP) behaviour, this research examined the connection between Chinese hotel employee's intrinsic motivation (IM), extrinsic motivation (EM), their intention to apply loyalty programme practices (LPP) in the Chinese hotel industry and lastly the degree to which Chinese hotel employees feel that LPP are relevant to them. Data was collected from 1047 hotel employees (893 final valid responses) in China. Path analysis was employed by SPSS Statistics 24 and Mplus 7.4 to test the proposed hypotheses. The findings suggest that both extrinsic and intrinsic motivation of Chinese hotel employees were found to have a positive impact on their intentions to adopt LPP. The employee's loyalty programme involvement mediated the above influence process. Theoretical and practical implications are also discussed.
Keywords: 350; employee management; hospitality industry; loyalty programme; motivation